The forgotten tragedy of unidentified dead in the Mediterranean. (May 2015) - Cattaneo, C.; Tidball Binz, M.; Penados, L.; Prieto, J.; Finegan, O.; Grandi, M.
Abstract: The need to identify the dead – an issue of paramount importance for the forensic sciences – and its importance for humanitarian, administrative, judicial and other purposes are universal values enshrined by domestic and international law. However, for hundreds of men, women and children, migrants, who die every year in their attempt to cross the Mediterranean Sea to reach Europe this fundamental right remains unfulfilled. In order to address and bring solutions to this tragedy the International Committee of the Red Cross (ICRC) carried out an assessment in 2012 and 2013 across European Mediterranean countries affected by irregular immigration across the sea (Italy, Greece, Malta, Portugal, France, Spain). An international meeting in 2013 among Southern European countries led to recommendations which should serve as a road-map for action. They are already guiding activities of the ICRC and other participant institutions. The Council of Europe, which endorsed the recommendations, has since stepped up its efforts to prevent and resolve the humanitarian consequences of migration, including the unidentified dead. Among other things it has called on its Member States to "set up a proper system of data collection of the mortal remains of people who lose their lives in the Mediterranean and make it swiftly accessible to relatives".